ANALISIS DAMPAK PENERAPAN KEBIJAKAN PELATIHAN PEGAWAI DALAM MENINGKATKAN KUALITAS PELAYANAN DI KANTOR CAMAT MORO’O KABUPATEN NIAS BARAT - Pria Mansyah Zalukhu; Syah Abadi Mendrofa; Yamolala Zega; Sukaaro Waruwu (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze the impact of the implementation of employee training policies on improving service quality and identify the inhibiting factors in the Moro'o District Office, West Nias Regency. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study show that the implementation of the training policy has not been running optimally and has not had a significant impact on improving the quality of public services. The form of training that is carried out is still general socialization, unstructured, and lacking in depth. The main inhibiting factors are budget limitations, less interesting and interactive methods of delivering materials, and weak support for the implementation of training results in the work environment. Based on these findings, it is recommended that the Moro'o District Office design a training program that is more structured, sustainable, and in accordance with the real needs of employees, and supported by adequate budget allocation and participatory training methods.